The Reasons for The Degradation of the Technological Structure of the National Economy of the Russian Federation in the 1990s. - V. Bodrova, E.; V. Kalinov, V. (International Journal of Engineering and Technology, 2018)
On the basis of published materials and archival documents, the extremely topical problem of determining the causes of the fall in innovation activity in the real economy, the catastrophic state of the country's scientific and technical complex in the context of the implementation of liberal reforms of the 1990s is investigated. Evaluations of leading experts are analyzed. It is concluded that as a result of flaws in conceptual approaches, poor management of scientific and technological activities, uncontrolled and forced privatization, implemented at the time of financial and credit, tax and pricing policies, completely insufficient state support, Russian fundamental and, especially, branch science was brought into a state of deep crisis, losing its accumulated potential, which caused irreparable damage to its economy and national security.Â Â